(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
The present study was undertaken to determine the effects of crude saponins extract of Parkia biglobosa fruit husk on gentamicin-induced nephrotoxicity in male Wistar rats. The study was aimed to determine the effects of crude saponins extract of Parkia biglobosa fruit-husk on some liver and kidney indices on gentamicin-induced nephrotoxicity in male Wistar rats. Nephrotoxicity was induced in male Wistar rats (80Â±20g) by intraperitoneal administration of 80 mg/kg b.w of gentamicin for 9 days. Forty-two male rats were divided into six groups of 7 each, as follows: group 1: normal control, group 2: negative control, group 3: standard control, groups 4 and 5 were gentamicin-induced nephrotoxic but treated with 400 mg/kg and 800 mg/kg b.w of crude saponins extract respectively. Group 6: received normal saline with 1200 mg/kg b.w of crude saponins extract. Administration of extract occurred daily for 12 days. A serum sample was used for the determination of kidney function parameters and liver function parameters. Kidney tissues were used for histological evaluations. At dose up to 500 mg/kg b.w does not cause any mortality or sign of toxicity. Thus the extract is considered safe. Gentamicin administration induced marked nephrotoxicity as evidenced by a significant increase (p< 0.05) in serum levels of creatinine, urea, uric acid and bun. A significant increase (p< 0.05) in ALT, ALP, AST, TP, GGT and ALB. Treatment of rats with crude saponins of Parkia biglobosa fruit-husk extract was found to improve kidney and liver indices, as well as histological changes in the kidney. Administration of crude saponins of Parkia biglobosa fruit husk extract was found to improve kidney and liver indices, as well as antioxidant activities and histological changes in the kidney.